Audubon on Louisiana : Selected Writings of John James Audubon - Audubon, John-James, (1785-1851) (Book collections on Project MUSE.)
"Audubon on Louisiana contains what the author considers Audubon's essential writings on Louisiana, demonstrating the crucial role of the state in his life."